2018
DOI: 10.1111/joss.12469
|View full text |Cite
|
Sign up to set email alerts
|

The influence of audiovisual stimuli cuing temperature, carbonation, and color on the categorization of freshness in beverages

Abstract: The study reported here investigated the influence of audiovisual stimuli signaling the likely temperature (the presence versus absence of ice cubes), the likely level of carbonation (the presence versus absence of bubbles), and the color of the liquid on the categorization of freshness in beverages. Participants made speeded categorization responses ("fresh" versus "not fresh") concerning the bimodal stimuli. When the stimuli were categorized as fresh, visible ice cubes decreased the participants' reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…The use of images as surrogates of the samples has been revealed useful in heterogeneous samples that might present small differences between individual portions and for those that experiment appearance changes with time, as observed by Maughan et al () studying the color of cooked turkey patties. The importance of the image in the prediction of the overall perception of sensory characteristics and consumers' behavior was tested by Roque et al () for refreshing attributes of beverages. They found that some of the visual stimuli studied contributed to the categorization of beverages as refreshing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of images as surrogates of the samples has been revealed useful in heterogeneous samples that might present small differences between individual portions and for those that experiment appearance changes with time, as observed by Maughan et al () studying the color of cooked turkey patties. The importance of the image in the prediction of the overall perception of sensory characteristics and consumers' behavior was tested by Roque et al () for refreshing attributes of beverages. They found that some of the visual stimuli studied contributed to the categorization of beverages as refreshing.…”
Section: Resultsmentioning
confidence: 99%
“…Once the consumer is in the purchasing situation and is evaluating the freshness of the product, the aspect of the product is a key factor on the perception of freshness. Therefore, the use of the image of the product as a replacement for the product itself might be a strategy to improve the use of sensory analysis on defining shelf life, since it allows for tests of products with different storage times at the same moment, requires fewer samples, and reaches the consumers through an internet platform, resulting in a general simplification of the logistics of a consumer test and a reduction of its costs The use of images as surrogates for samples in sensory evaluation of appearance has been tested with fruit salad (Manzocco, Rumignani, & Lagazio, ), cooked turkey patties (Maughan, Chambers, & Sandria, ), and beverages (Roque, Lafraire, & Spence, ). To our knowledge, there are no previous reports on the use of images of chicken meat to evaluate the perception of freshness by the consumer.…”
Section: Introductionmentioning
confidence: 99%
“…In the direct task, the visual and auditory stimuli that the participants had to discriminate were presented in the task's instructions. It is thus possible that during the processing of these stimuli along the task, the participants formed higher order associations between the target stimuli and the corresponding category to which they might relate (e.g., freshness perception in beverages, or positively correlated psychophysiological concept such as thirst-quenching, see [21,32]). According to this interpretation of our results, the pitch-size correspondence effects reported in the case of beverages might be driven by top-down influences such as attentional processes.…”
Section: Resultsmentioning
confidence: 99%
“…Pictures were taken in the same laboratory conditions in order to control for the light, room temperature, and ambient liquid temperature. All the pictures were taken when the liquid motion was stabilized and the foam was absent at the surface of the liquid (i.e., 2 s after pouring the 200 mL volume) since a negative effect of the foam on the participants' RTs (reaction times) was found in previous research [21]. The picture in which the bubbles were the most visually identifiable was selected.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation